Theory of plasticity - Chakrabarty, J. (Elsevier/Butterworth-Heinemann, 2006)
Plasticity is concerned with the mechanics of materials deformed beyond their elastic limit. A strong knowledge of plasticity is essential for engineers. This title presents material on the use of computational methods, including coverage of developments in cyclic plasticity and soil plasticity. It is intended for academics and professionals.